2021
DOI: 10.1002/anie.202100301
|View full text |Cite
|
Sign up to set email alerts
|

Red to Near‐Infrared Mechanochromism from Metal‐free Polycrystals: Noncovalent Conformational Locks Facilitating Wide‐Range Redshift

Abstract: Figure 5. a) Normalized PL spectra of MPCbZ during the hand-actuated grinding process. b) Powder X-ray diffraction (PXRD) patterns and time-resolved spectra c) of Re-phase in the pristine state and after slight and full grinding. d) The absorption spectra of MPCbZ in the Rephase and full-grinding state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(51 citation statements)
references
References 52 publications
1
50
0
Order By: Relevance
“…[ 368b ] In fact, PL color changes upon external stimuli can be considerable with maximum shifts of ≈0.5 eV, [ 203,282 ] for instance blue↔green, light‐blue↔yellow, green↔red, [ 369 ] or, as recently reported, red↔near infrared. [ 370 ] Even more pronounced color shifts can be achieved by using co‐crystal strategies, as discussed in the following.…”
Section: Luminescent Crystalline Materialsmentioning
confidence: 99%
“…[ 368b ] In fact, PL color changes upon external stimuli can be considerable with maximum shifts of ≈0.5 eV, [ 203,282 ] for instance blue↔green, light‐blue↔yellow, green↔red, [ 369 ] or, as recently reported, red↔near infrared. [ 370 ] Even more pronounced color shifts can be achieved by using co‐crystal strategies, as discussed in the following.…”
Section: Luminescent Crystalline Materialsmentioning
confidence: 99%
“…[67][68][69][70][71][72][73][74][75][76] Zhu et al reported a benzothiadiazole based luminogen that exhibits a spectral shift of 160 nm on grinding. 77 Larger spectral shift results in high contrast mechanochromism and hence is useful for fabricating strain sensing devices. 78 In recent years, organic molecules comprising of an electron-donor (D) moiety and an electron acceptor (A) moiety have surfaced as promising candidates for mechanoresponsive materials.…”
Section: Rajneesh Misramentioning
confidence: 99%
“…67–76 Zhu et al reported a benzothiadiazole based luminogen that exhibits a spectral shift of 160 nm on grinding. 77 Larger spectral shift results in high contrast mechanochromism and hence is useful for fabricating strain sensing devices. 78…”
Section: Introductionmentioning
confidence: 99%
“…3d). 45 Two polymorphic crystals 4-R (P2 1 /c) and 4-N (P1 ¯) were obtained from a dichloromethane/hexane mixed solution of 4 and showed red and NIR emission at 615 and 727 nm, respectively. In response to grinding stimuli, the fluorescence maximum of 4-R changed to 775 nm.…”
Section: Crystengcomm Highlightmentioning
confidence: 99%